Translation and Validation of the Albanian Version of the Psychosocial Impact of Dental Aesthetics Questionnaire in Kosovo - Shahiqi, Donika Ilijazi; Kelmendi, Jeta; Anic-Milosevic, Sandra (European Journal of General Dentistry, 2024)
Objective Modern orthodontics is shifting from being doctor centric to patient centric, and understanding the impact of malocclusion from patient's perspective is very important. To accomplish this, questionnaires that assess the psychosocial effects of malocclusion must be validated in the original language of the respondents. The purpose of this study is translation, validation, and cross-cultural adaptation of the psychosocial impact of dental aesthetics questionnaire (PIDAQ) into the Albanian language.Materials and Methods The PIDAQ questionnaire was translated into Albanian, back translated, pretested, cross-culturally adapted, and finally delivered to 130 subjects (38% males) aged between 18 and 30 years (mean age 24.3 ± 3.7). A dentist, previously calibrated, evaluated the orthodontic treatment needs of each subject by using the dental health and aesthetics component of the Orthodontic Treatment Need Index (IOTN). In this study, the internal consistency, test–retest reliability, discriminant validity, and responsiveness were assessed.Results Albanian version of PIDAQ shows satisfactory internal consistency (α ranging from 0.90 to 0.96) with high test–retest reliability (r > 0.98). The discriminant validity revealed that subjects with minor and severe malocclusion according to IOTN categorization had different PIDAQ scores (p < 0.001). Among the domains of PIDAQ, the subscale of dental self-confidence detected differences in psychosocial impact related to orthodontic treatment during the testing of responsiveness (p < 0.001).Conclusion The PIDAQ in Albania showed strong psychometric characteristics. It is suitable for use in the Albanian cultural context.
Keywords: validity; reliability; malocclusion; quality of life; dental aesthetics